Analysing Business Value of Two Indian Pharma Majors - Ramana kumar, Dr.; Sreekanth, K.P.V.B. (Journal of Contemporary Research in Management (JCRM), 2013)
This paper â€œCorporate Valuationâ€ gives a brief idea about Analyzing the Balance Sheet and Profit and Loss Account of two pharmaceutical companies to know the performance of the companies. The Profit and Loss accounts and Balance Sheets of pharmaceutical companies are taken into account to know the firmâ€™s value. For the calculation of the value of the firm Discounted Cash Flow method has been adopted. In this method following steps have been considered 1. Calculation of free cash flow, 2. Calculation of the cost of capital, 3. Calculation of Continuing value of the firm, 4. Calculation of firm value.